PENGARUH SOCIAL MEDIA MARKETING MELALUI BLACKBERRY MESSENGER TERHADAP MINAT BELI KONSUMEN DI PT AGUNG AUTOMALL (AGUNG TOYOTA) HARAPAN RAYA PEKANBARU - Lian Pratama; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The rise of social media is the new media can be used as marketing at once to do consumer interaction, called social media marketing. One of the social media marketing which is now popular among business people, IE blackberry messenger. Through this application can send a message text, sound, and images for free about their business or place information and promotions offered from their products so that it formed an interest to buy from someone, with the blackberry messenger messages or information submitted can attract the attention of consumers so that it appears consumer interest was bought from them. It is utilized by the sales marketing PT Agung Automall (Agung Toyota) Harapan Raya Pekanbaru, to draw the attention or interest of consumers buy in blackberry messenger. The purpose of this study, i.e. to find out how big the influence of social media marketing through blackberry messsenger against consumer interest in buying PT Agung Automall (Agung Toyota) Harapan Raya Pekanbaru. The theory used in this research is the theory of S-O-R by Hovland and the concept of social media marketing as a supporter. The methods used in this study i.e. quantitative empirical research methods. Researchers gather data using questionnaires and documentation. The location of this research, PT Agung Automall (Agung Toyota) Harapan Raya located at JL. h. Imam Munandar/Harapan Raya Tip No. 13 Pekanbaru. The number of samples for the study that is as much as 91 respondents, using the technique of withdrawal sample Simple Random Sampling. For the sake of knowing how big the influence both of these variables, the researchers used a simple linear regression analysis. While the test questionnaire for data processing, is done using Statistics program Product anf Service Solution (SPSS)20 version of Windows. Based on the results of a simple linear regression for the study of the influence of social media marketing through blackberry messenger consumer buying interest against the PT Agung Automall (Agung Toyota) Harapan Raya Pekanbaru, the regression coefficient values obtained in this study were Y = 0.548 X + with 2.442 level significance 0.000. Of course smaller than α = 0.05. That is, there is the influence of social media marketing through blackberry messenger consumer buying interest against the PT Agung Automall (Agung Toyota) Harapan Raya Pekanbaru 55.3% and enter influencial in the category of being. H0 is rejected and thus Ha is received.JOM